Correlation of refractory hypoxemia with biochemical markers and clinical outcomes of COVID-19 patients in a developing country: A retrospective observational study: Running head: Predictors of hypoxemia in COVID-19. Issue 1 (2nd January 2021) - Asghar, Muhammad Sohaib; Ahmed, Iftekhar; Alvi, Haris; Iqbal, Sadia; Khan, Ismail; Alvi, Rabia Seher; Saeed, Zara; Irfan, Saboohi; Akhtar, Maria; Fatima, Ibraj
ABSTRACT: Introduction: COVID-19 is mainly a respiratory illness, causing hypoxemia in the majority of those been infected. In our study, we aimed to correlate the biochemical markers with hypoxemia and predicting the prognosis of COVID-19 patients. Materials and methods: A retrospective, observational study was conducted to include all the admitted COVID-19 patients (n = 183) diagnosed by a real-time Polymerase chain reaction and evaluated those for hypoxemia and disease outcomes by utilizing the biochemical markers. Results: Out of the 183 patients, 117 were in the ward, 66 were in ICU, 148 of them recovered, while 35 deaths were reported, 89 patients were having persisting hypoxemia (despite oxygen therapy) during the hospital stay, and the remaining 94 were non-hypoxemic with or without supplemental oxygen therapy. There were significant differences in mean hemoglobin (p = 0.028), total leukocyte count (p = 0.005), Neutrophil-to-Lymphocyte ratio (p = 0.001), serum urea and creatinine (p = 0.002), serum potassium (p = 0.009), C-reactive protein (p = 0.001), Lactate dehydrogenase (p = 0.005), and Ferritin (p = 0.042) of the hypoxemic patients versus non-hypoxemic group. Amongst the deceased patients, there was significant leukocytosis (p = 0.008), increased Neutrophil-to-Lymphocyte ratio (p = 0.001), elevated C-reactive protein (p = 0.001), and Lactate dehydrogenase (p = 0.009). Receiver operating characteristic curves showed Neutrophil-to-Lymphocyte ratio (p < 0.001), C-reactive protein (p < 0.001), and Lactate dehydrogenase (p < 0.001) most significantly associated with hypoxemia and death. Conclusion: The inflammatory markers are a good guide for predicting the hypoxemia and disease outcome. The results concluded Neutrophil-to-Lymphocyte ratio, C-reactive protein, and Lactate dehydrogenase were effective biomarkers in predicting a severe course of COVID-19, but could not establish significant associations of serum Ferritin, Procalcitonin, and D-Dimer.